Analisis Kegagalan Struktur Crosspiece pada Mesin Cuci Front Loading Berdasarkan Simulasi Finitte Element Analysis (FEA) - Achmad Ilham Prabowo; Muhammad Lubis Abdillah; Elisa Sulistyorini (International Forum of Researchers and Lecturers, 2026)
The crosspiece (spider arm) is a critical component of a front-loading washing machine that connects the drum and shaft while supporting dynamic loads during washing and spinning. Continuous exposure to centrifugal forces, unbalanced loads, and cyclic stresses may cause fatigue failure. This study analyzes the structural performance and fatigue behavior of an ADC12 aluminum alloy crosspiece through numerical simulation and experimental testing. Finite Element Analysis (FEA) was used to evaluate stress distribution, strain, deformation, and safety factors under spinning conditions, while fatigue analysis estimated component service life. Hardness testing was also conducted after aging and chemical treatments to assess changes in material properties. The results showed a maximum Von Mises stress of 72.40 MPa at the hub-arm junction, with maximum strain and deformation of 56.50 × 10⁻⁶ and 3.58 × 10⁻³ mm, respectively. The minimum safety factor was 3.87, indicating safe structural performance. Fatigue analysis predicted a service life of approximately 5 × 10⁶ cycles, with the crosspiece arm as the most critical region. The highest hardness, 158 HRB, was obtained after 70 hours of aging combined with chemical treatment. Overall, the design meets structural safety requirements but remains susceptible to fatigue failure at the hub-arm junction.